Narrative Features and Cultural Motifs in a Cautionary Tradition from Mangaia (Cook Islands). - Reilly, Michael (Waka Kuaka, 2016)
A cautionary narrative taken from a 20th-century collection of Cook Islands oral traditions recounts the mistreatment of a daughter, Pataariri, by her chiefly father, KÅtuku, and his consequential death caused by a spirit power putting matters to rights. This paper highlights narrative features such as repetition, expansion, images and gestures, as well as the cultural valuing of the protection of vulnerable people by those in authority. Failure to look after others could result in spiritual interventions that admonished or even killed the perpetrators, a cultural form of policing behaviours that still operates today.